2021
DOI: 10.46989/001c.29495
|View full text |Cite
|
Sign up to set email alerts
|

Structure, proximate composition, nutrient dynamics and growth characteristics of Penaeus vannamei in indoor biofloc systems with three different salinities and carbon sources

Abstract: In the biofloc systems the continuous application of carbon sources led to the assimilation of nitrogenous nutrients and formation of heterotrophic bacterial biomass. The present experiment was conducted in 0.22m 3 capacity tanks in the triplicate to find out the structure, proximate composition, nutrient dynamics and growth characteristics of Penaeus vannamei in indoor biofloc systems with three different salinities (35, 20 and 5ppt) and carbon sources (molasses, sugar and rice flour) with an estimated C:N r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Most studies have shown that under high-N supplies, rice's nutritive growth period is prolonged relative to the reproductive growth period, which results in symptoms such as late maturity, plant collapse, a lower percentage of filling, and ineffective tillering [9][10][11]. In addition, the heavy application of N fertilizers can adversely affect biodiversity, human health, and climate and pose a major challenge to N cycles [12,13]. China is the world's largest consumer of N fertilizer, and the N fertilizer utilization rate is only 30-40%, which is 15-20% lower than that of other major riceproducing countries [14].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have shown that under high-N supplies, rice's nutritive growth period is prolonged relative to the reproductive growth period, which results in symptoms such as late maturity, plant collapse, a lower percentage of filling, and ineffective tillering [9][10][11]. In addition, the heavy application of N fertilizers can adversely affect biodiversity, human health, and climate and pose a major challenge to N cycles [12,13]. China is the world's largest consumer of N fertilizer, and the N fertilizer utilization rate is only 30-40%, which is 15-20% lower than that of other major riceproducing countries [14].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, insufficient nitrogen fertilizer affects rice photosynthesis, which results in reduced yield [7,8]. While higher nitrogen fertilizer input can help to increase rice yield, it reduces nitrogen use efficiency, adversely affecting biodiversity, human health, and climate and posing a significant challenge to the nitrogen cycle [9,10]. China is the world's largest consumer of nitrogen fertilizer and has a nitrogen use efficiency of only 30-40%, which is 15-20% lower than other major rice-producing countries [11].…”
Section: Introductionmentioning
confidence: 99%